Gás não convencional no Brasil: dificuldades e oportunidades - COSTA, Joice Daise de Sousa (2018)
Technological and economic factors generated a revolution in the oil sector with a successful exploration of shale gas. Exploitation had attracted the worldwide attention, including Brazil. Currently, because of unconventional resources USA is one of the most important oil producers. This work aims to study the role of unconventional resources in the context of Brazilian oil policy. Firstly, it must differentiate between conventional natural gas reservoirs from non-conventional ones. Secondly, it shows the main characteristics of reservoirs, with emphasis on non-conventional reservoirs, showing their formation and lithology. Thirdly, it presents exploration technique called fracking method, which is usual for such reservoirs. Fourthly, it explains the current situation of shale gas in Brazil after the 12th round, its main basins their potential and estimated reserves. Fifthly, the work ends showing the current situation of unconventional gas in the Brazilian market, benefits and barriers for the exploration and production, and an analysis of the environmental risks and what is necessary for an optimal exploitation of such energy resource in Brazil.